Polarization Sensitive Solar‐Blind Ultraviolet Photodetectors Based on Ultrawide Bandgap KNb3O8 Nanobelt with Fringe‐Like Atomic Lattice (Adv. Funct. Mater. 24/2022). (8th June 2022) - Ping, Yue; Long, Haoran; Liu, Hui; Chen, Chao; Zhang, Nannan; Jing, Hongmei; Lu, Jiangbo; Zhao, Yiwei; Yang, Zimeng; Li, Wei; Ma, Fei; Fang, Xiaosheng; et al.
Abstract : Solar‐Blind Ultraviolet Photodetectors In article number 2111673, Xiaosheng Fang, Zhongming Wei, Hua Xu, and co‐workers fabricate a polarization sensitive solar‐blind ultraviolet photodetector based on ultrathin KNb3 O8 nanobelts synthesized via chemical vapor deposition growth. The device exhibits superior photodetection performance in the solar‐blind ultraviolet region (230–280 nm) with high responsivity (30 A W −1 ) and large linear dichroic ratio (1.62).